Apatinib: A Novel Antiangiogenic Drug in Monotherapy or Combination Immunotherapy for Digestive System Malignancies - Li, Haosheng; Huang, Haiyan; Zhang, Tao; Feng, Haoran; Wang, Shaodong; Zhang, Yaqi; Ji, Xiaopin; Cheng, Xi; Zhao, Ren (Frontiers in Immunology, 2022)
Digestive system malignancies (DSMs) are one of the primary causes of cancer-related death. Meanwhile, angiogenesis has been proved to play an important role in the process of cancer neovascularization. Apatinib, a novel targeted antiangiogenic molecule, could generate highly selective competition in the vascular endothelial growth factor receptor-2 (VEGFR-2), involved in tumor progression and metastasis. It has been implied as a promising cancer treatment agent that can prevent tumor cell proliferation meanwhile inhibit tumor angiogenesis. Furthermore, completed clinical trials demonstrated that apatinib could prolong the progression-free survival and overall survival in advanced gastric cancer and primary liver cancer. Recent studies revealed that apatinib had a synergistic effect with immunotherapy as a second-line and third-line treatment regimen for some other cancers. In this review, we summarize the pharmacological properties of apatinib and the latest clinical application in chemotherapy-refractory patients with advanced digestive system cancer. Based on the comparable survival results, the molecular mechanisms of apatinib are prospective to include the antiangiogenic, apoptosis-inducing, and autophagy-inducing properties in the corresponding signaling pathway. Treatment of apatinib monotherapy or combination immunotherapy remains the optimal option for patients with DSMs in the future.